Analisis Pengaruh Beban Kerja, Stres Kerja, Kelelahan Kerja, dan Lingkungan Kerja Terhadap Kinerja Tenaga Medis - Haidar Ferdian Ilyasa; Naniek Ratni Juliardi A.R (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Doctors and nurses play role in achieving goals of hospital, optimal service. They’re must pay attention to resulting performance. Each individual has different workload related to fatigue and work stress, and supported by work environment. The purpose of this study is to determine level of independent variables and their impact on performance, along with recommendations. The method used is multiple linear regression of results by questionnaire distributed to 57 doctors and 174 nurses. The results of analysis showed that average value of mental workload was 3.60 in high category, work stress was 83.37 in moderate category, fatigue was 29.61 in moderate category, work environment was 22.16 in good condition, and performance was 8.40 in high category. Simultaneously the independent variables have a significant influence on performance of doctors and nurses with an Fcount of 29.481. Partial workload has positive and significant effect on performance with Tcount of 3.372. Work stress has negative and significant effect with Tcount of -3.709. Work fatigue also has negative and significant effect with Tcount of -3.805. Work environment has positive and significant effect with Tcount of 6.766. Optimizing performance can be done by controlling administrative hazards that adjust to hospital policies that have previously implemented.